Pola Degradasi Protein Kasar Rumput Rawa pada Kerbau Rawa secara In Sacco - Armina Fariani; Ahmad B Praramadhan; G Muslim; Anggriawan NT Pratama (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Fariani A, Praramadhan AB, Muslim G, Pramana ANT. 2021. Degradation pattern of crude protein Swamp grasses on swamp buffalo by in sacco. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 219-227. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). This study aims was to determine the degradation pattern of crude protein content of Kumpai minyak (Hymenachne amplexicaulis), Kumpai tembaga (Hymenachne acutigluma), Sendayan (Rhinchospora corymbosa) and Bento rayap This research was conducted from February to July 2020 at the Animal Nutrition and Forage Laboratory, Department of Animal Technology and Industry, Faculty of Agriculture, Sriwijaya University. This research was conducted by in sacco method using a completely randomized design (CRD) method with 4 treatments and 3 replications. The parameter observed was the degradation of crude protein by in sacco using a fistulated Pampangan swamp buffalo. Based on the results of the study showed that the value of crude protein degradability was significantly different (P<0.05) on each grass evaluated. The value of fraction a was the fraction easily degraded with the highest value of crude protein degradability found on Kumpai minyak (37.15%); the value of fraction b was the slow degraded fraction, the lowest value was on Sendayan (17.12%) and the value of c was the rate degradation fraction b with the highest value found on Bento rayap (0.13%).The highest degradation value during 48 hour incubation period was found on Kumpai Minyak grass (60.04%).